A philosophical perspective on generic אלהים in the Hebrew bible in relation to the classical theory of concepts - Gericke, Jaco (Journal for semitics, 2014)
Contemporary analyses of אלהים as generic concept tend to be based on psychological theories of concepts. This article, by contrast, attempts to show what a philosophical analysis of the concept of generic אלהים in the Hebrew Bible is concerned with when approached from the perspective of the classical or definitionist view of conceptual structure. However, rather than offering a conceptual analysis of generic אלהים in any given context, the discussion features a general meta-conceptual overview of the classical theory and the pros and cons of applying it to the concept in question.